The sister of the South / 4. - Rodda, Emily (Rodda, Emily. Dragons of Deltora, 2005)
Lief, Barda, and Jasmine have successfully destroyed three of the Four Sisters, evil Shadow Lord creations that are poisoning their land. Now they must head to the city of Del where Sister of the South lies hidden.